2021
DOI: 10.1186/s12883-021-02259-9
|View full text |Cite
|
Sign up to set email alerts
|

Low dose statins improve prognosis of ischemic stroke patients with intravenous thrombolysis

Abstract: Background For acute ischaemic stroke patients, it is uncertain whether intravenous thrombolysis combined with statins might increase the therapeutic effect. Additionally, using high-intensity statins after thrombolysis may increase the risk of bleeding in patients. Asian stroke patients often take low-dose statins. It is speculated that reducing the dose of statins may improve the risk of bleeding. Methods Data from consecutive acute ischaemic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Statin use was related to an improved short-term NIHSS score in this study, and the effect was signi cant in most subgroups. These results are consistent with study involving ischaemic stroke patients with thrombolysis 7,11 and with other studies of ischaemic stroke populations 12 . The LDL value in the statin group after admission was opposite to that before admission, lower than that in the control group, and the proportion of patients with an LDL level reaching the guideline standard was also higher than that in the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Statin use was related to an improved short-term NIHSS score in this study, and the effect was signi cant in most subgroups. These results are consistent with study involving ischaemic stroke patients with thrombolysis 7,11 and with other studies of ischaemic stroke populations 12 . The LDL value in the statin group after admission was opposite to that before admission, lower than that in the control group, and the proportion of patients with an LDL level reaching the guideline standard was also higher than that in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…But the results was a subgroup analysis and the study included a lesser patients. In our previous studies, low-dose statins were associated with good functional outcomes in patients with recurrent stroke or thrombolysis treatment, but patients with thrombectomy were not included 6,7 . Overall, in patients with ischaemic stroke undergoing intra-arterial thrombectomy, it is unknown whether low-dose statin is related to prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among the included 22 studies ( 23 44 ), there were 2 post-hoc analyses of RCTs ( 35 , 40 ), 13 prospective cohort studies ( 24 , 27 – 29 , 31 , 33 , 34 , 37 39 , 42 44 ), and 7 retrospective cohort studies ( 23 , 25 , 26 , 30 , 32 , 36 , 40 ). The 22 included studies were published from 2007 to 2021, with sample sizes ranging from 55 to 4,012 participants and a total of 17,554 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies ( 24 27 , 30 , 31 , 35 , 38 , 41 ) involving 4,115 patients reported outcomes according to in-hospital statin use. The pooled estimates showed that in-hospital statin use was associated with a lower likelihood of symptomatic ICH (five studies, OR 0.46; 95% CI 0.21–1.00; p = 0.045; p for Cochran Q statistic = 0.88, I 2 = 0%; Figure 3A ; Table 3 ), any ICH (three studies, OR 0.51; 95% CI 0.27–0.98; p = 0.04; p for Cochran Q statistic = 0.53, I 2 = 0%; Figure 3B ; Table 3 ), and 3-month mortality (five studies, OR 0.42; 95% CI 0.29–0.62; p < 0.001; p for Cochran Q statistic = 0.44, I 2 = 0%; Figure 3C ; Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has demonstrated that the efficacy of LMDS for cardiovascular disease (CVD) patients in Asia, such as GOALLS study, STATT study, and RAEL-CAD study ( 9 , 13 - 15 ). Similarly, in regards to AIS, our previous studies have indicated that AIS patients after reperfusion therapies treated with a low-dose statin (LDS) in west China had a better prognosis compared with non-statin ( 16 - 18 ). However, the correlation between LMDS use and prognosis has not been evaluated in AIS patients with conventional medication treatment alone.…”
Section: Introductionmentioning
confidence: 97%